2017
DOI: 10.1186/s12904-017-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, psychological burden, needs, and satisfaction during specialized inpatient palliative care in family caregivers of advanced cancer patients

Abstract: BackgroundThis pilot study aimed to investigate quality of life, psychological burden, unmet needs, and care satisfaction in family caregivers of advanced cancer patients (FCs) during specialized inpatient palliative care (SIPC) and to test feasibility and acceptance of the questionnaire survey.MethodsDuring a period of 12 weeks, FCs were recruited consecutively within 72 h after the patient’s admission. They completed validated scales on several outcomes: quality of life (SF-8), distress (DT), anxiety (GAD-7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
3
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 46 publications
6
120
3
23
Order By: Relevance
“…Psychiatric involvement in end‐of‐life care is becoming more widely appreciated due to severe symptoms at end of life . This was mirrored in our results by greater lifetime psychotropic usage and consultation in transplant patients that had end‐of‐life disease progression and died.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Psychiatric involvement in end‐of‐life care is becoming more widely appreciated due to severe symptoms at end of life . This was mirrored in our results by greater lifetime psychotropic usage and consultation in transplant patients that had end‐of‐life disease progression and died.…”
Section: Discussionsupporting
confidence: 65%
“…Psychiatric involvement in end-of-life care is becoming more widely appreciated due to severe symptoms at end of life. [44][45][46] In addition to the limitations and future studies previously discussed, other notable constraints included the data set being from a single transplant center, which may limit the generalizability of the study, and an analysis of retrospective data. The binary psychopharmacologic variable study design also limits conclusions about the differential indication for psychotropic usage over time and specific inciting events.…”
Section: Hospital and Medical Factorsmentioning
confidence: 99%
“…Given this context, it is important to emphasize female hegemony in informal care, representing 84% of this group, being mostly daughters and wives (10)(11)(12) . With regard to familial relationship, this study had three daughters, two mothers and a grandmother, attesting that the responsibility for care still remains as an attribute of the feminine universe.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Germany observed a certain psychological burden in family caregivers of patients with advanced cancer during palliative care, evidenced by feelings of distress, sadness and anxiety reported by these caregivers (12) . Therefore, it is noticed that the caring for the relative raises emotional problems in the caregivers, which are somatized and expressed in the physical body.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic implementation of relevant tools to assess carers' needs and facilitate personalised careplans and/or regular screening for carer distress remains challenging within current service delivery models (Alvariza et al 2018). Although caring for a loved family member can be both rewarding and fulfilling, the evidence repeatedly suggests that some carers suffer negative health consequences because of their role (Ates et al 2018;Hudson and Payne 2011;Hudson and Aranda 2014;Ullrich et al 2017). Hudson and colleagues systematically reviewed instruments related to family caregivers of patients with palliative care needs (Hudson, Trauer et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%